Global Logistics And Distribution Planning : Strategies for Management - Waters, Donald (Routledge, 2018)
The fully revised new edition of this well known and respected book is characterized by the more international perspective it has taken on through contributions from internationally known authors and a final section on international logistics which examines in turn strategies for West and East Europe, the Far East and North America.Logistics has a key strategic role to play in the long-term plans of major companies, and is recognized as a vital part of every organization. To a large extent this crucial new role is due to an expanded view of logistics, which now includes all the activities related to the supply chain from initial suppliers through to final customers.This book provides a wealth of useful ideas and practical information on all the current and future trends in logistics and distribution. Written by a host of contributors drawn from industry, constancy and education, this book provides new insights into the most significant aspects of logistics, including:developments in logisticssupply chain strategieslean logisticsefficient customer responselogistics in different countriespartnering and strategic alliancesre-engineering the logistics functionFrom logistics professionals, consultants, professors and students to managers from different backgrounds who want an appreciation of current trends in the subject, this book is essential reading.About the author: Donald Waters, a past member if the Institute of Logistics and currently a member of the Canadian Association of Logistics Management, has lectured weekly on logistics, operational research and management science, and has brought his academic career to fruition as Professor of Operations Management at the University Calgary, Canada. He is also the author of Operations Management in the Kogan Page Fast Track MBA Series. Features.- Resumé vydavatel
Keywords: distribuce zboží; logistika (management); distribution of goods; business logistics; sborníky; elektronické knihy; papers of several authors; electronic books